2016
DOI: 10.1364/oe.24.017562
|View full text |Cite
|
Sign up to set email alerts
|

Tensile-strained Ge/SiGe quantum-well photodetectors on silicon substrates with extended infrared response

Abstract: We report on tensile-strained Ge/Si0.11Ge0.89 quantum-well (QW) metal-semiconductor-metal (MSM) photodetectors on Si substrates. A tensile strain of 0.21% is introduced into the Ge wells by growing the QW stack on in-situ annealed Ge-on-Si virtual substrates (VS). The optical characterization of Ge/Si0.11Ge0.89 QW MSM photodetectors indicates that the optical response increases to a wavelength of 1.5 μm or higher owing to the strain-induced direct bandgap shrinkage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The fabrication process can be started on a silicon substrate by deposition of the Aluminum bottom contact as stated in [11], followed by deposition of the Germanium and Si0.1Ge0.9 bottom buffer layers and then two Germanium quantum wells. [12,13] This process will be continued by deposition of the Gold metal strip, which can be taken from [13] and again a similar process to the bottom Ge/SiGe layers [12,13] and finally deposition of top Aluminum contact. [11] The fabricated structure can then be connected to a metal/insulator/metal (MIM) or insulator/metal/insulator (IMI) waveguide or even be used in far field lasing mode.…”
Section: Fig1 3d Schematics Of Proposed Nanolasermentioning
confidence: 99%
“…The fabrication process can be started on a silicon substrate by deposition of the Aluminum bottom contact as stated in [11], followed by deposition of the Germanium and Si0.1Ge0.9 bottom buffer layers and then two Germanium quantum wells. [12,13] This process will be continued by deposition of the Gold metal strip, which can be taken from [13] and again a similar process to the bottom Ge/SiGe layers [12,13] and finally deposition of top Aluminum contact. [11] The fabricated structure can then be connected to a metal/insulator/metal (MIM) or insulator/metal/insulator (IMI) waveguide or even be used in far field lasing mode.…”
Section: Fig1 3d Schematics Of Proposed Nanolasermentioning
confidence: 99%
“…Moreover, it can be coupled into silicon-based waveguides similar to [15] or used in the far-field configuration in which plasmon modes will be converted into photons through the cavity interface. Our device benefits from a metal-semiconductor-metal-semiconductor (MSMS) structure, which can perform well in the 1550 nm regime by means of incorporating highly doped strained Ge quantum wells as the direct bandgap gain medium [33,34]. Design characteristics of this structure can be found in Table 2.…”
Section: Proposed Nanoresonator Structuresmentioning
confidence: 99%
“…It should be noticed that for transforming germanium into a direct bandgap material, strong tensile strain levels could be applied in the fabrication process. This will reduce the Г-valley direct bandgap of the material below the L-valley indirect bandgap (0.664 eV) [33,34]. This will result in an output wavelength about several micrometers in which efficient plasmonic nanocavities cannot be designed.…”
Section: Proposed Nanoresonator Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, by investigating the photodiodes with different diameter values of 50, 30, 20, 16 and 12 µm, the work established that the detection bandwidth of the larger diodes was limited by the RC time constant; however, for the smallest diodes the detection bandwidth limitation was due to Ge/SiGe MQW carrier dynamics that the carriers need to escape out of the QWs before reaching p-and n-doped regions [78,79]. As the early Ge/SiGe MQW photodetector operated optimally up to an optical wavelength of approximately 1500 nm, Onaran et al [80] and Chang et al [81] demonstrated the use of tensile strain to extend the optimal detection wavelength of the Ge/SiGe MQWs to be within the C-band wavelength region. The low responsivity values of 0.01 A/W at 1550 nm reported by Onaran et al [80] from tested surfaced-illuminated photodiodes could be improved by increasing the number of MQW periods or by employing a waveguide configuration to increase the optical absorption length.…”
Section: Optical Detection From Ge/sige Mqwsmentioning
confidence: 99%